PENGARUH MEDIA AUDIO VISUAL PADA PEMBELAJARAN PENDIDIKAN AGAMA KATOLIK MELALUI MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA KELAS X SMK RAIMANUK TAHUN AJARAN 2023/2024 - Hale, Erpilia; Yata Mones, Anselmus; Habu Lelo, Elmagondulfa (Kanisius, 2024)
Audio Visual learning media is a learning medium that presents audio elements and visual elements simultaneously so that students get messages or information from visualizations both in the form of words and pictures equipped with sound. Currently, the younger generation is required to be able to keep up with the times, both in terms of technology, social, and culture. The younger generation does not have skills due to technological developments so that they can harm themselves and the people around them. The skills that must be needed are critical thinking skills, problem-solving skills and scientific argumentation skills. So one of the efforts that can be made to improve this situation is to run a problem-based learning model. Therefore, this study aims to find out (1). Is there an Effect of the Use of Audio Visual Media on the Learning Outcomes of Class X Catholic Religious Education Students at SMK Border Raimanuk? (2). To find out if there is an Effect of the Problem-Based Learning Model on the Learning Outcomes of Catholic Religious Education Students Class X SMK Border Raimanuk? The type of method used in this study is a correlational descriptive approach. The location of the research is at the Raimanuk Border Vocational School. The informants in this study are grade X students, the data collection techniques used are pratest, posstest and questionnaire distribution. Meanwhile, data analysis techniques include classical assumption test analysis techniques and statistical tests. The results of the study showed that almost all students in class X experienced an increase in learning outcomes after applying audio-visual media with a problem-based learning model by the researchers. It is known that the number in the initial test is 1579%, increased in the final test by 2717%, and the average from the initial test is 45.11%, increased in the final test by 77.62%. This shows that students experience improved learning outcomes